Histoid leprosy on scrotal skin: an unusual case - Paudyal, P; Shrestha, S; Agarwal, M; Kafle, SU; Karki, S; Upadhyaya, P; Agarwal, S; Pradhan, A (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Although no part of the skin is immune from invasion by mycobacterium leprae it is commonly seen over cooler parts of the body and very rarely found over external genitalia because of their warm temperature. Histoid leprosy is rare but a well-defined entity with specific clinical, histopathological, and bacteriological features. CASE REPORT: A Punch biopsy measuring 3x3 cm of a 73 year old male having an erythematous plaque over scrotum since 2 months was received for histopathologic examination with the clinical differentials of pilomatrixoma and steatocystoma multiplex. Histopathologic and special stain slides revealed a feature of histoid leprosy. CONCLUSION: Although rare, leprosy lesions may occur on the male genitalia and therefore in all male patients, history taking and examination of external genitalia should not be neglected. DOI: http://dx.doi.org/10.3126/ijim.v2i2.8325 Int J Infect Microbiol 2013;2(2):64-67